Model Sistem Dinamis Dalam Meningkatkan Efisiensi Rantai Pasok Telur Ayam Di Bojonegoro - Jose Bagus Ramadhan; Gilang Hayu Rahmawan; Taris Nur Rahmah; Seftin Fitri Ana Wati (Universitas Pahlawan Tuanku Tambusai, 2024)
This study proposes the application of a dynamic systems model to enhance the efficiency of the chicken egg supply chain in Bojonegoro. The egg supply chain in this region often faces challenges in effective inventory management and distribution. The dynamic systems model is designed to simulate the complex dynamics of supply, demand, and distribution processes. Historical data on egg supply from the past several months are utilized to develop and validate this model. Through simulation and sensitivity analysis, the research aims to identify optimal strategies in inventory management, pricing adjustments, and production planning to improve supply chain efficiency and sustainability. Implementation of this model is expected to assist producers, distributors, and traders in optimizing their operations, reducing logistics costs, and enhancing customer satisfaction through improved product availability and consistent delivery times.